Community Urgent Care Use Following Implementation of the Veterans Affairs Maintaining Internal Systems and Strengthening Integrated Outside Networks Act. Issue 6 (June 2021) - Vashi, Anita A.; Urech, Tracy; Wu, Siqi; Boothroyd, Derek; Mehta, Paril; Dalton, Aaron L.; Brill, Elizabeth; Kessler, Chad; Asch, Steven M.
Abstract : Background: Effective June 6, 2019, Veterans Affairs (VA) began offering a new urgent care (UC) benefit that provides eligible Veterans with greater choice and access to care for the treatment of minor injuries and illnesses in their local communities. Objectives: The aim was to describe trends in UC use, identify predictors of UC benefit use, and understand the factors associated with community UC use versus VA emergency department (ED) or urgent care center (UCC) use. Study Design: Using VA administrative data, this was a retrospective cross-sectional study of Veterans that were enrolled in VA in FY19. Veterans were classified into 3 groups: UC benefit users, benefit non-users, and VA ED/UCC users. Methods: We used summary statistics to compare population characteristics across user groups. To determine whether predisposing, enabling, and need factors predicted UC benefit use and setting choice (community UCC vs. VA ED/UCC), 2 logistic regression models were fitted to assess odds of UC use. Results: From June 6, 2019 through February 29, 2020, 138, 305 Veterans made 175, 821 community UC visits. The majority of visits were made by White males who were not subject to co-pays. The average cost to VA for UC visits was $132 (SD=$135). Upper respiratory infections were the most common reason for UC use. Being younger, female, and living farther from a VA ED/UCC was associated with greater UC benefit use compared with both benefit non-users and VA ED/UCC users. Conclusions: The new benefit expands Veteran access to UC services for low-acuity conditions.